Overview of neonatal sepsis in an Intensive Care Unit: a literature review (Research, Society and Development, 2023)
Neonatal sepsis is considered a systemic inflammatory response syndrome caused by suspected or confirmed infection, being one of the main causes of neonatal death worldwide and one of the main causes of increased neonatal mortality. In Brazil, on average, 3,000 children die each year from neonatal sepsis, with prematurity being na additional risk factor. Objective: to understand through the literature about sepsis in newborns. Methodology: this is a literature review study, according to pre-established criteria for selection and exclusion of articles. We opted for more recently published articles that answered the guiding question: “What has been disclosed about the development of sepsis in pediatric patients”. Results: Neonatal sepsis can be classified as early (PNS), in which it occurs in the first 48 to 72 hours of life; or late (SNT), which occurs after 72 hours. SNP can be caused by maternal risk factors and/or interactions during childbirth or neonatal, while SNT holds the main risk factors inherent in the newborn. Clinical manifestations are very variable and nonspecific, which makes the diagnosis of neonatal sepsis difficult. Complementary tests are based on collection of blood and cerebrospinal fluid and, in late sepsis, urine culture. Given the diagnosis, treatment is carried out through empirical antibiotic therapy. Conclusion: the detailed and continuous observation of the newborn, its clinical signs and risk factors is fundamental for the morbidity and mortality of neonatal sepsis to be reduced.